Strategi Pembinaan Yayasan Az-Zahrah Terhadap Pembentukan Karakter Dan Akhlak Bagi Peserta Didik - Yuniar Putri Utami; Eni Murdiati; Hidayat HT (Social Science and Contemporary Issues Journal, 2023)
To realize the character building program, a strategic plan for character and moral development for students is needed. The research entitled "Az-Zahrah Foundation Development Strategy for the Formation of Character and Morals for Students". The purpose of the research is to find out about the Az-Zahrah Foundation's Development Strategy for Character and Moral Formation and the factors that influence the Az-Zahrah Foundation's Development Strategy for Character and Moral Formation for Students. This type of research is qualitative research. Data collection techniques include observation, interviews and documentation. Then data analysis techniques such as data reduction, data presentation and drawing conclusions. The results of the study show that (1) there are seven coaching strategies in forming character and morals that are inseparable from the delivery of religious material in religious activities, professional coaches will always instill disciplinary values in students so that they prioritize religious activities and exemplify commendable behavior, so that students are able to become good children care about the environment, achievement and noble character. (2) Az Zahrah schools have adequate facilities such as religious activities available prayer rooms, mosques, and places for special religious activities that support, then there is also the implementation of da'wah in schools that have sufficient funds so that students are very enthusiastic about participating in religious activities during class hours has been completed, as well as the existence of professional teachers in fostering and providing advice, so as to be able to realize students with good character and morals at the Az Zahrah Palembang Foundation school